2013
DOI: 10.3762/bjnano.4.19
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning preparation and electrical and biological properties of ferrocene/poly(vinylpyrrolidone) composite nanofibers

Abstract: SummaryNanofibers containing ferrocene (Fc) have been prepared for the first time by electrospinning. In this paper, Fc was dispersed uniformly throughout the poly(vinypyrrolidone) (PVP) matrix for the purpose of combining the properties of PVP and Fc. The effects of solvents and Fc concentration on the morphologies and diameters of nanofibers were investigated. In the DMF/ethanol solvent, the morphologies of the obtained nanofibers significantly changed with the increase of Fc concentration. The results demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Among other studies reported in the literature, there are some examples which provide information on the thermal stability of the ferrocene-containing polymers both in the inert atmosphere and in air. These reports contain the temperatures at which the thermal decomposition of the polymers started [5][6][7][8][9]. In addition, de Souza et al proposed the degradation mechanism of ferrocene-containing polyamides in air from the FTIR spectra of the residues at various temperatures: 150, 210, and 350 C [10].…”
Section: Introductionmentioning
confidence: 99%
“…Among other studies reported in the literature, there are some examples which provide information on the thermal stability of the ferrocene-containing polymers both in the inert atmosphere and in air. These reports contain the temperatures at which the thermal decomposition of the polymers started [5][6][7][8][9]. In addition, de Souza et al proposed the degradation mechanism of ferrocene-containing polyamides in air from the FTIR spectra of the residues at various temperatures: 150, 210, and 350 C [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal degradation of the sample shows a behavior that resembles that of PVP found in literature. 44 PVP could be dominant as it has the highest thermal stability in comparison to other constituents in the sample. The major weight loss between 380°C and 460°C can be assigned to normal thermal decomposition of PVP.…”
Section: Tga For the Pvp-drug-loaded Double Layermentioning
confidence: 99%
“…As shown in Figure , the degradation process of the PMCh/PET, PMCh/PET/Fc‐1, and PMCh/PET/Fc‐2 electrospun fibers were investigated with TGA from 25 to 900°C in nitrogen gas. Because of the evaporation of adsorbed water or moisture, the TGA results of all of the samples showed a first weight loss of 5–10% before approximately 100°C . The TGA curves of Fc‐1 and Fc‐2 each showed one decomposition stage between approximately 130 and 400°C, as shown in Figure .…”
Section: Resultsmentioning
confidence: 91%
“…Recent scientific research has focused on the study of both ferrocene‐derived nanofibers and chitosan nanofibers via electrospinning technology . To the best of our knowledge, chitosan nanofibers containing ferrocenyl‐substituted N ‐acetyl‐2‐pyrazoline derivatives prepared via electrospinning have not been reported up to this point.…”
Section: Introductionmentioning
confidence: 99%